Implementation of JSON Web Token on Authentication with HMAC SHA-256 Algorithm - Ficry Cahya Ramdani; Rahmi Nur Shofa; Alam Rahmatulloh (Sistemasi: Jurnal Sistem Informasi, 2023)
The rapid growth of information technology is influenced by globalization to accelerate access to information. This creates new problems, as differences must produce relevant information. Of course, system integration will be required. Web Service is a system integration solution that does not consider the platform, architecture, or programming language used in different sources. The security of web service is considered not yet implemented. The JSON Web Token (JWT) technology is an authentication mechanism for web service and will have a significant impact on data security. This implementation optimizes JWT security with the HMAC SHA-256 algorithm. Testing is conducted on two information systems by comparing the performance size when JWT technology is applied to Tim Bebersih Masjid Information System. The results show that the implementation of JWT on Windows Server 2019 (VM) is 462.8 ms with an average data size of 8.59 kb. Testing on the Windows 10 operating system obtained an average speed of 216.25 ms with an average data size of 8.59 kb. The result on Windows Server 2019 (VM) from the JWT performance test itself obtained the highest result, due to the use of virtual machine which is considered to consume a lot of RAM, resulting in performance that is 2 times higher.Keywords: Algorithm, HMAC SHA-256, JSON Web Token, Web Service, Virtual Machine